Analysis of an arbitrarily rotated slot on a conducting spherical cavity - Khoomwong, Ekajit; Phongcharoenpanich, Chuwong (My University, 2007)
The formulation for analyzing an arbitrarily rotated rectangular slot antenna at arbitrary location on a conducting spherical cavity is considered by using the technique of dyadic Green's function. The convergence tests of solutions and some radiation characteristics are investigated for various cases when the physical parameters, such as slot orientations and wide range of cavity sizes, are changed.